The relationship between mental health literacy and depression among older adults in Selangor - Badrol Hisham, Afaf Qamelia; Zainal Abidin, Muhammad Adil; Mohd Tohit, Nor Faiza; Rusli, Mohammad Farhan; Abdul Khaiyom, Jamilah Hanum (Community Health Society Malaysia, 2024)
Background: Depression is prevalent among the older adults but often misdiagnosed. Improving mental health literacy could enhance early detection and treatment, increasing awareness, and improving outcomes for the disorder. This research aim to measure the prevalence of depression, its determinants and relationship with mental health literacy among older adults in Selangor. Material and Methods: A state-wide cross sectional study was conducted involving the Selangor state residents from June 2022 until June 2023 using the state health mobile application (Selangkah) which is accessible in all apps stores. A validated questionnaire to screen users' levels of depression using the validated Geriatric Depression Scale-15 and Mental Health Literacy Scale (MHLS) was used to measure the literacy level. Results: More than 918 elderly completed the study with the prevalence of depression among Selangor older adults was 30.0%. The mean mental health literacy score was 99, indicating a moderate level of mental health literacy. The risk factor for depression were higher education level, widowed/divorced while mental health literacy was the protective factor. The predictors for higher mental health literacy score were female and those with lower depression score. Conclusion: The results revealed a high prevalence of depression due to higher mental health literacy level. Mental health literacy enhanced the understanding, early screening, and this improving early access to early support and treatment which can improve older adults well- being. The study advocates for improving mental health literacy initiatives through collaboration between the Selangor State Government and universities to address the findings and support the mental well-being of the older adults.